2021
DOI: 10.1038/s41598-021-96433-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the feasibility of explainable computer-aided detection of cardiomegaly on chest radiographs using deep learning

Abstract: We examined the feasibility of explainable computer-aided detection of cardiomegaly in routine clinical practice using segmentation-based methods. Overall, 793 retrospectively acquired posterior–anterior (PA) chest X-ray images (CXRs) of 793 patients were used to train deep learning (DL) models for lung and heart segmentation. The training dataset included PA CXRs from two public datasets and in-house PA CXRs. Two fully automated segmentation-based methods using state-of-the-art DL models for lung and heart se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…Erroneous results are a problem faced by all DL models in scenarios where the contours are not clearly demarcated, as such cardiac contour has a more major impact than the thoracic contour. 22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erroneous results are a problem faced by all DL models in scenarios where the contours are not clearly demarcated, as such cardiac contour has a more major impact than the thoracic contour. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Erroneous results are a problem faced by all DL models in scenarios where the contours are not clearly demarcated, as such cardiac contour has a more major impact than the thoracic contour. 22 Saiviroonporn et al 23 used the VGG-16 U-Net model to assess the impact of AI-enabled reporting of CTR. Their findings concluded that AI alone had higher variations than human readers, but it could support the radiologist by reducing observer variation and operation time.…”
Section: Discussionmentioning
confidence: 99%
“…The extracted regions of interest are subsequently used to compute the CTR and a threshold of 0.50 is used in order to distinguish between normal and cardiomegaly instances. A similar approach consisting of optimizing 2 distinctive segmentation models in order to extract both cardiac and thoracic areas of interest before computing the CTR is proposed by Lee et al ( 2021 ).…”
Section: Related Workmentioning
confidence: 99%
“…Although classical image processing-based studies have reported promising results on limited private datasets, these methods lack generalization ability, making them inefficient for real-time application. On the other hand, deep learning-based methods have made vast inroads into various computer-aided medical applications [16], such as disease detection [17] and the segmentation of affected regions [18]. Consequently, deep learning has also been applied for mandibular canal segmentation to boost performance.…”
Section: Related Workmentioning
confidence: 99%